Level Of Implementation Of Integrated Farming (A Case in P4S An-Nabawie Agrolestari Majasuka Village Palasah District Majalengka Regency) - Sulaksana, Jaka; Susanto, Hermawan; Umyati, Sri (Green Publisher, 2023)
The purpose of this research is to find out the description of the application of integrated farming systems in efforts to develop agribusiness and also to determine the level of application of integrated agricultural systems in efforts to develop agribusiness. This research was conducted in Majasuka Village, Palasah District, Majalengka Regency. The analytical method used, namely descriptive analysis, is intended to find out how the description of the application of integrated agricultural systems and the level of implementation of integrated agricultural systems in the development of agribusiness efforts. The results showed that the level of application of integrated agricultural systems in the development of agribusiness is quite high with an average total conformity rate of 80%. the respondent farmers have been quite good about integrated farming systems in an effort to develop agribusiness.